2003
DOI: 10.1089/089426803772455631
|View full text |Cite
|
Sign up to set email alerts
|

Lung Deposition and Respirable Mass During Wet Nebulization

Abstract: For metered dose inhalers (MDIs), high-flow cascade impaction with a United States Pharmacopia (USP) throat provides a useful prediction of in vivo lung and oropharyngeal aerosol deposition. Particles expected to deposit in the lung are included in the "fine particle fraction" measured on the bench. Comparable in vitro standards are not available for nebulizers. The present study compared aerosol deposition in an in vitro model using low-flow cascade impaction with deposition in vivo in human subjects. A low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 6 publications
1
40
1
Order By: Relevance
“…6,7,9,10 Harris and Smaldone 10 demonstrated that, as an accessory for a jet nebulizer, the front-loaded mask configuration was more efficient than the bottom-loaded mask configuration, which is in contrast to our study. Our data showed that the designs of the face masks we tested do not influence aerosol delivery with a VMN at the flows tested.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…6,7,9,10 Harris and Smaldone 10 demonstrated that, as an accessory for a jet nebulizer, the front-loaded mask configuration was more efficient than the bottom-loaded mask configuration, which is in contrast to our study. Our data showed that the designs of the face masks we tested do not influence aerosol delivery with a VMN at the flows tested.…”
Section: Discussioncontrasting
confidence: 95%
“…Studies have shown that the design of the face mask affects the amount of aerosolized drug delivery. [6][7][8] The deposition of aerosolized drug delivered with a face mask through a high-flow heated humidified oxygen system has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…34 Hence, even if the ultrasonic nebulizer gave the largest particle size, all 3 types of nebulizers proved satisfactory according to this criterion. Sangwan et al 35 compared 2 jet nebulizers and found respirable fractions of 6% and 14%. Skaria et al 36 compared the respirable fraction of a vibrating mesh nebulizer (Omron NE U22) with the Sidestream.…”
Section: Particle Size Distribution and Respirable Fractionmentioning
confidence: 99%
“…Hess et al 8 showed that the AeroEclipse nebulizer produced more fine particle mass (percent of particles Ͻ 4.7 m multiplied by total aerosol output) than commercially available SVNs. Sangwan and colleagues 22 conducted in vivo and in vitro comparisons of a standard SVN and the AeroEclipse nebulizer. The in vitro experiment showed that the AeroEclipse generated smaller particles than the SVN in both a standing cloud and during ventilation.…”
Section: Discussionmentioning
confidence: 99%